Packaging potential of Ipomoea batatas and κ‐carrageenan biobased composite edible film: Its rheological, physicomechanical, barrier and optical characterization. Issue 2 (11th December 2020) - Bharti, Sanjay Kumar; Pathak, Vikas; Arya, Anita; Alam, Tanweer; Rajkumar, Vincentraju; Verma, Arun Kumar
Abstract: The present study aimed at developing composite edible film from a blend of Ipomoea batatas, κ‐carrageenan, and glycerol. Three different treatments by varying glycerol concentrations (5%‐TS1, 10%‐TS2 & 15%‐TS3) in film‐forming solution were prepared and resultant films were evaluated for rheological, physicomechanical, barrier, and optical properties. All the treatments showed film‐forming ability with varying degrees of distinction. The steady rheology of film‐forming solution containing 10 and 15% glycerol in gel state showed non‐Newtonian fluid behavior. Film solubility improved significantly ( p < .01) with glycerol; however water vapor permeability of films had an intermediate value, comparable to other films reported in literature. Mechanical properties of films were excellent in terms of tensile strength, which reached 15 N/mm 2 . The films presented good optical properties relating to hunter colorimeter. Therefore, the composite blend of I. batatas and κ‐carrageenan can be tailored with glycerol concentration to apply as edible film over different foods. Practical applications: The demerits associated with plastics have eventually led researchers' to explore natural alternatives. Edible films are one of the prospering substitutes, but the films prepared from single polymer films are lacking mechanical strength. The composite blend of Ipomoea batatas and κ‐carrageenan is having promising competence to be mold as packaging film with enhanced physicomechanical properties. Glycerol concentration is having an undeviating impact on physicomechanical properties of the film. Therefore, film processing protocol can be stringently controlled to have product‐specific films for practical commercial applications.